THE CORRELATION BETWEEN WRITING SKILL AND VOCABULARY MASTERY DESCRIPTIVE TEXT OF VII GRADE SMPN 2 PADALARANG - Erni Trinita; Evie Kareviati (IKIP Siliwangi, 2023)
This study aimed to identify the correlation betweenÂ writing skills of class VII students and their oral knowledge of the material. The object of this study is 64 students of VII grade SMPN in Padalarang. The method of this research is quantitative. The writer utilized a multiple-choice exam that comprised 30 test items to assess the student master's vocabulary results. This study indicated that the mean for the student was 65,12 more than the intended mean 53,5 in vocabulary degree. The average writing capability of pupils was 60.76 around the optimum norm of 70. The result shows that the correlation between vocabulary knowledge and the skill of composing text is favourable and substantial. It indicates that knowledge of vocabulary impacts the capacity of writing.Â Keywords:Â Writing Skill; Vocabulary Mastery; Correlation